Critical Discourse Analysis on Nadia Omara Podcast - Muftiah; Ulinsa; Arum Pujining Tyas; Yunidar; Juliah Marfuah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyze the structure of discourse on Nadia Omara's podcast using the Critical Discourse Analysis (AWK) model of Teun A. Van Dijk. The focus of this research is to examine the macrostructure, superstructure, and microstructure in the podcast narrative, especially in the episode "Kalomba" from Central Sulawesi. This study uses a qualitative descriptive method with data in the form of narrative text obtained through direct observation of podcasts. The collection technique carried out is by collecting data by listening, watching, and taking notes, then followed by data analysis techniques using Van Dijk's social cognition approach and Miles and Huberman's interactive analysis model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that in the macro structure, the main theme raised is the mystical experience experienced by a family in a remote area that reflects people's belief in folklore and urban legends. In the superstructure, it was found that podcasts are systematically arranged through introductions, content, and closing sections so that they are able to build tension and emotional engagement of listeners. Meanwhile, in the microstructure, the use of semantic elements (setting, detail, intent, and presumption), syntax (inductive and coherent sentences), as well as stylistic and rhetorical elements such as expressive diction, hyperbole, and rhetorical questions are found to be effective in strengthening the horror atmosphere.